Outcomes of observation as therapy for pelvic organ prolapse: A study in the natural history of pelvic organ prolapse12. Issue 4 (20th August 2012) - Gilchrist, Alienor S.; Campbell, William; Steele, Hannah; Brazell, Hema; Foote, Jonathon; Swift, Steven
Abstract Aims To determine the rate of progression or regression of pelvic organ prolapse (POP) in subjects with symptomatic POP who decline intervention (pessary or surgery) and elect observation. Methods Sixty‐four patients choosing observation as primary management of symptomatic POP were followed with sequential pelvic organ prolapse quantification (POP‐Q) exams. A change in the leading edge value of ±≥2 cm was considered significant. POP‐Q exam results, choice of therapy and symptom severity at last visit were recorded. Results The leading vaginal edge POP‐Q exam value at initial exam ranged from −1.5 to 7 cm. Distribution of patients by POP‐Q stages on initial exam was: stage I: 1%, stage II: 31%, stage III: 31%, and stage IV: 1.78% (50/64) of patients demonstrated no change in leading edge value from first to last visit on POP‐Q exams. Nineteen percent (12/64) demonstrated progression (≥2 cm increase in leading edge); 3% (2/64) demonstrated regression (≥2 cm decrease in leading edge). Median follow‐up was 16 months (range 6–91 months). On multivariate analysis, no variable, including length of follow‐up, was associated with change in leading edge value (P = 0.09, data not shown). At their last recorded visit, 63% (40/64) of subjects continued observation, 38% (24/64) desired a pessary trial or surgical correction. Those desiring intervention had no greater worsening of prolapse on exam at last follow‐up compared with subjects who continued observation. Conclusion The natural history of pelvic organ prolapse is most often one of very minimal change in subjects who decline intervention (pessary or surgery) and choose observation. Neurourol. Urodynam. 32: 383–386, 2013. © 2012 Wiley Periodicals, Inc.